2018
DOI: 10.1116/1.5030507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RF plasma modification on the thermal and mechanical properties of electrospun chitosan/poly(vinyl alcohol) nanofiber mats

Abstract: On the design and fabrication of biomedical devices, the mechanical integrity and the thermal stability of the materials used are of paramount consideration. In this study, the effects of 13.56 MHz radio frequency plasma modification using argon (Ar) and oxygen (O2) discharges on the morphology, thermal properties, and tensile properties of the nonwoven electrospun chitosan/poly(vinyl alcohol) nanofiber mats were investigated. The scanning electron microscope images showed a significant change in the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In another study, Latag et al studied the impact of Ar or O 2 cold plasma treatments of CS/PVA nanofibers on their mechanical properties. 171 Results showed that Young's modulus was significantly more influenced by O 2 plasma treatment than by Ar plasma treatment. Indeed, the decrease of Young's Modulus was 2.1-times higher after O 2 plasma treatment compared to Ar one.…”
Section: Cold Plasma Treatment Of Electrospunmentioning
confidence: 94%
See 3 more Smart Citations
“…In another study, Latag et al studied the impact of Ar or O 2 cold plasma treatments of CS/PVA nanofibers on their mechanical properties. 171 Results showed that Young's modulus was significantly more influenced by O 2 plasma treatment than by Ar plasma treatment. Indeed, the decrease of Young's Modulus was 2.1-times higher after O 2 plasma treatment compared to Ar one.…”
Section: Cold Plasma Treatment Of Electrospunmentioning
confidence: 94%
“…In terms of elongation at break, cold plasma treatment of polymer nanofibers tends to lead to a decrease of this parameter, which means an increase in stiffness, in each case of plasma surface modification such as formation of plasma polymer, 1 1 8 cross-linking, 1 2 4 , 1 4 2 or surface etching. 87,88,99,118,171 For example, as for Young's modulus, the decrease of elongation at break of low-pressure cold plasma treated CS/PVA nanofibers was 1.6-times higher for O 2 plasma treatment compared to Ar one. 171 This was again explained by the increase in friability of the materials.…”
Section: Cold Plasma Treatment Of Electrospunmentioning
confidence: 97%
See 2 more Smart Citations
“…The exposed particles and photons in the polymer surface can be modulated by factors such as the plasma operating parameters, polymer substrate, gas chemistry, and the reactor design [117]. The excited plasma species continuously bombard the polymer surface, resulting to the change in the chemistry and characteristics of the surface structure and/or morphology [118,119]. The plasma and surface interaction may result to different processes such as functionalization, crosslinking, and etching.…”
Section: Plasma-materials Interactionsmentioning
confidence: 99%